Extending expectancy-value theory predictions of achievement and aspirations in science: Dimensional comparison processes and expectancy-by-value interactions. (June 2017) - Guo, Jiesi; Marsh, Herbert W.; Parker, Philip D.; Morin, Alexandre J.S.; Dicke, Theresa
Abstract: Based on TIMSS data (18, 047 Grade 8 students from the four OECD countries that collected data for multiple science domains), this study integrated dimensional comparison theory and expectancy-value theory and tested predictions about how self-concept and value are related to achievement and coursework aspirations across four science domains (physics, chemistry, earth science, and biology). First, strong support for social comparisons suggested that high achievement in a particular domain enhance students' motivation in the same domain, which in turn predicted domain-specific aspirations. Particularly, self-concept significantly interacted with value to predict aspirations. Second, in the processes underlying the formation of self-concept and intrinsic value, students tended to engage in negative dimensional comparisons between contrasting domains (physics vs. biology) but positive dimensional comparisons between assimilating domains (physics vs. chemistry). Similar dimensional comparison processes were evident for the effects of self-concept and intrinsic value on aspirations. The results generalized well across all countries. Highlights: Students engaged in contrasting and dimensional comparisons across science domains. Such processes were evident for effects of achievement on self-concept and value. Similar processes were found for effects of self-concept and value on aspirations. Self-concept significantly interacted with value to predict aspirations. The results generalized well across four OECD countries.